Effects of infliximab on markers of inflammation and bone turnover and associations with bone mineral density in patients with ankylosing spondylitis. Issue 2 (21st May 2008) - Visvanathan, S; van der Heijde, D; Deodhar, A; Wagner, C; Baker, D G; Han, J; Braun, J
Abstract : Objectives: To evaluate the relationship between bone mineral density (BMD) and biomarkers of bone turnover and inflammation in patients with ankylosing spondylitis (AS) treated with infliximab. Methods: Patients (n = 279) were randomly assigned (3:8) to receive placebo or 5 mg/kg infliximab every 6 weeks through week 96. At week 24, placebo-treated patients crossed over to infliximab 5 mg/kg. Starting at week 36, patients treated with infliximab received dose escalations to 7.5 mg/kg. Hip and spine BMD were measured (baseline, week 24, week 102) using dual-energy x -ray absorptiometry. Sera were analysed (baseline, week 24, week 102) for levels of bone alkaline phosphatase (BAP), osteocalcin, C-terminal cross-linking telopeptide of type I collagen (CTX), interleukin-6 (IL-6), vascular endothelial growth factor (VEGF) and transforming growth factor-β. Results: Patients treated with infliximab showed significantly greater median increases in BMD of the spine (2.5%, p<0.001) and hip (0.5%, p = 0.033) at week 24 than those who received placebo (0.5% and 0.2% respectively). Baseline levels of IL-6, VEGF, osteocalcin, BAP and CTX were significantly correlated with increases in spinal BMD at weeks 24 and 102 in the infliximab group. In a multiple regression analysis, high baseline osteocalcin levels and early increases in BAP at week 2 were significantly associated with increases in BMD scores of the spine (week 102) and hip (weeks 24 and 102) in the infliximab group. Conclusions: Patients with AS who received infliximab showed significant increases in BMD scores over 2 years. While many significant correlations were observed between BMD scores of the hip and spine and biomarker levels, high baseline osteocalcin levels and early increases in BAP were consistently associated with increases in BMD scores.